Business models of Chinese firms impacted by the crisis based on case studies - Lin, Zhongshu; Li, Xueyao; Lau, Yeng Wai; Lau, Wei Theng; Mohammed Shah, Sabarina (Richtmann Publishing, 2024)
The Covid-19 pandemic has hit businesses extremely hard. Because of reduced social contact, many business models (BMs) have been limited, and some have become unviable. In the current external crisis, timely BM changes are crucial for more effective responses to challenges of critical importance. Based on the resourcebased view theory, this study adopts a multi-case study approach to investigate the core competencies demonstrated by firms in different industries in adjusting to the external environment. Integrating and adapting existing BMs to form new BMs presents significant differences in operational outcomes between firms. This study focuses on the response and development of firm crisis management during the Covid- 19 pandemic. Successful BM can enable firms to survive the crisis and even achieve improvement in the crisis. In addition, this paper distinguishes between business model innovation (BMI) and business model adaptation (BMA) at the theoretical and substantive levels, mainly from the perspective of firm value, including value proposition, value creation, value capture and value transfer, to differentiate between BMI and BMA. This study explains the impact of various BM changes on sustainable firm profitability and value through a detailed collection of media and company official reports. The emphasis on strategic flexibility has positively impacted firm BMs and value, which has implications for providing insights into companies’ longterm development.